The Role of Attitudes, Affect, and Income in Predicting COVID-19 Behavioral Intentions - Clemens, Kelly S.; Matkovic, John; Faasse, Kate; Geers, Andrew L. (Frontiers in Psychology, 2021)
Handwashing is important in preventing infectious diseases like COVID-19. The current public health emergency has required rapid implementation of increased handwashing in the general public; however, rapidly changing health behavior, especially on this scale, is difficult. This study considers attitudes and affective responses to handwashing as possible factors predicting COVID-19 related changes to handwashing behavior, future intentions, and readiness to change during the early stages of the pandemic in the U.S. Income was explored as a potential moderator to these relationships. To explore these issues, data from 344 community participants, also analyzed by Matkovic and colleagues (2020) to address other questions, was examined. Results indicate that stronger affective responses toward handwashing relate to increases in handwashing since the outbreak of COVID-19, and both attitudes and affect uniquely predict handwashing intentions. Income significantly moderated the relationship between affect and readiness to change. Those with low income were more influenced by both affective responses and attitudes. These results suggest messages targeting both cognitions and affective responses are needed to increase handwashing behavior during a global pandemic and these variables are critical in increasing readiness to change in low-income individuals.